PENGEMBANGAN APLIKASI MOBILE INTERAKTIF NARRATIVE TEXT & STORYTELLING BAHASA INGGRIS - Akhmad Alimudin; Aliv Faizal M (NJCA (Nusantara Journal of Computers and Its Applications), 2016)
Teaching the English language has become part of the curriculum in Indonesia. Listening is one of the skills in a language that needs special attention so that learners can improve listening skill. Narrative is a genre-based text that is part of a high school English teaching materials. The ability of the students in understanding the narrative text through listening skills need attention. Thus, we need a media that can assist participants in improving students' listening skills, especially English language support on a matter of narrative text. In connection with the widespread use of smartphones by high school students, then a mobile application that can be used by students in support of improving listening skills need to be made. So the researchers developed an android application which presents a narrative text with a focus listening folklore in Indonesia so that later can be accessed easily by the students so that smartphone users can use it to improve listening skills.